Breakthroughs in Technical Analysis : New Thinking From the World's Top Minds. - Keller, David (Bloomberg Professional., 2007)
Technical analysts build trading strategies based on trends and patterns in the markets' movements. Their task requires mastery of the world's markets and an understanding of the latest techniques. Breakthroughs in Technical Analysis reveals the new trading methods used by the world's top technicians. Building on the success of New Thinking in Technical Analysis (Bloomberg Press, 2000), this book, edited by Bloomberg L.P.'s own expert on technical analysis, David Keller, brings together market masters from the around the world. Some of their techniques have never left their country's borders b.